2002
DOI: 10.1038/sj.leu.2402424
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CD20-dependent cellular cytotoxicity by G-CSF-stimulated neutrophils

Abstract: Rituximab, a chimeric CD20 monoclonal antibody (mAb), is widely used in the treatment of patients with low-grade nonHodgkin's lymphoma. Possible anti-tumour mechanisms involve complement-mediated lysis and/or antibody-dependent cellular cytotoxicity (ADCC). Because G-CSF greatly enhances the cytotoxicity of neutrophils (PMN) in ADCC, the clinical efficacy of rituximab might be enhanced by the addition of G-CSF. Therefore, we investigated the neutrophil-mediated CD20-dependent cellular cytotoxicity in B cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 28 publications
4
45
1
Order By: Relevance
“…Although in our study the influence of G-CSF on the expression of FcgRIIIa NK was not investigated, we did find a decrease in the expression of FcgRIIIb on neutrophils from all patients. Since we previously demonstrated that ADCC of G-CSF-stimulated neutrophils on B cells was mediated mainly by FcgRI, 28 we do not think that the decrease in FcgRIIIb expression on the neutrophils influenced the response to the combination of rituximab and G-CSF in this study.…”
Section: Safety and Efficacy Of Rituximab Plus G-csf Le Van Der Kolk mentioning
confidence: 63%
See 1 more Smart Citation
“…Although in our study the influence of G-CSF on the expression of FcgRIIIa NK was not investigated, we did find a decrease in the expression of FcgRIIIb on neutrophils from all patients. Since we previously demonstrated that ADCC of G-CSF-stimulated neutrophils on B cells was mediated mainly by FcgRI, 28 we do not think that the decrease in FcgRIIIb expression on the neutrophils influenced the response to the combination of rituximab and G-CSF in this study.…”
Section: Safety and Efficacy Of Rituximab Plus G-csf Le Van Der Kolk mentioning
confidence: 63%
“…20 We found however, that chimeric CD20 mAbs were capable of inducing ADCC in B cells with G-CSF-primed neutrophils as effector cells, whereas unstimulated neutrophils could not induce CD20-dependent ADCC. 28 Thus, as intended, G-CSF administration resulted in FcgRI-positive, cytotoxic neutrophils. Last systemic chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only phase II studies or preliminary data are available preventing any definitive conclusions (Davis et al, 2000b;Kimby, 2002). Phase I trials combining rituximab with other cytokines such as IL-2, IL-12, granulocyte-colony stimulating factor and granulocyte macrophage colonystimulating factor have shown promising preliminary results that need to be confirmed in phases II trials (van der Kolk et al, 2002;Eisenbeis et al, 2004).…”
Section: Rituximab In Combination With Cytokinesmentioning
confidence: 99%
“…FcgRIIIb is the most abundant Fcg receptor on neutrophils, but evidence suggests that it is not involved in efficient tumor cell cytotoxicity (15). Antibody-dependent killing of tumor cells by neutrophils in the absence of G-CSF is described to be nonexistent or weak (16,17) and is likely mediated through FcgRIIa (18). Therefore, specific targeting of FcgRI has been proposed, as this may overcome potential inhibitory signals through FcgRIIb when IgG mAbs are employed (19).…”
Section: Most Clinically Used Mabs Belong To the Igg Subclass And Thementioning
confidence: 99%